A Review on Wearable Electrospun Polymeric Piezoelectric Sensors and Energy Harvesters. Issue 1 (25th October 2022) - Mirjalali, Sheyda; Mahdavi Varposhti, Arezo; Abrishami, Shayan; Bagherzadeh, Roohollah; Asadnia, Mohsen; Huang, Shujuan; Peng, Shuhua; Wang, Chun‐Hui; Wu, Shuying
Abstract: In recent years, wearable sensors and energy harvesters have shown great potential for a wide range of applications in personalized healthcare, robotics, and human–machine interfaces. Among different types of materials used in wearable electronics, piezoelectric materials have gained enormous attention due to their exclusive ability to harvest energy from ambient sources. Piezoelectric materials can be utilized as sensing elements in wearable sensors while harvesting biomechanical energy. Electrospun piezoelectric polymer nanofibers are extensively investigated due to their high flexibility, ease of processing, biocompatibility, and higher piezoelectric property (in contrast to their corresponding cast films). However, as compared to piezoceramic materials, they mostly exhibit relatively lower piezoelectric coefficients. Therefore, considerable efforts have been devoted to improving the piezoelectricity of electrospun polymer nanofibers recently, resulting in significant advances. This review presents a broad overview of these advances including new material, structure designs as well as new strategies to enhance piezoelectricity of electrospun polymer nanofibers. The challenges in achieving high mechanical performance as well as high piezoelectricity are particularly discussed. The main motivation of this review is to examine these challenges and highlight effective approaches to achieving high‐performance piezoelectric sensors and energy harvesters for wearable technologies. Abstract : Piezoelectric materials, particularly, electrospun polymeric nanofibers have been demonstrated as promising materials in developing wearable sensors and energy harvesters. This review presents an overview of recent efforts to improve the piezoelectric and mechanical properties of polymeric nanofibers via material and structural design.